Attitudes Towards Statistics as Study Matter and Tool for Data Analysis - Acón Araya, Siufong; Salazar Ramos, Marianela (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
A quantitative research, non-experimental design and descriptive scope was conducted with a sample of 303 students from the Faculties of Exact Sciences, Health Sciences and Social Sciences (Universidad Latina de Costa Rica), in which was sought to recognize the attitudes they have towards statistics as a subject of study and as a tool for understanding everyday situations. The scale of Estrada (2002) was used. Reliability α = 0.87 was obtained. It is determined that the main dimension regarding the perception of statistics is the affective one. Positive attitudes toward statistics were more frequently found in students of exact sciences, even though all students consider that statistics not only serve this group.